Book Review: Sequence Stratigraphy and Characterization of Carbonate Reservoir - Herman Darman (Ikatan Ahli Geologi Indonesia, 1998)
Sequence Stratigraphy and Characterization of Carbonate ReservoirBy Charles Kerans and Scott W. Tinker (1977), 130 p., Published by SEPM (Society for Sedimentary Geology) Short Course Note No. 40l 1731 E. 71st Street, Tulsa, OK 74136-5108. Fax: (1-918)-493-2093; http: www.sepm.org; ISBN 1056576-040-9; Price US34 (member), US48 List